Epidemiology of pediatric acute mastoiditis in Israel: A National Registry 10‐year perspective. Issue 6 (17th October 2022) - Samuel, Orit; Saliba, Walid; Stein, Nili; Shiner, Yotam; Cohen‐Kerem, Raanan
Abstract: Background and Objectives: Previous small studies have proposed a higher incidence of acute mastoiditis in Israeli pediatric patients than in other Western countries. The aim of this study was to describe the incidence of acute mastoiditis and its epidemiological features over a decade, in order to identify variables that could possibly affect the incidence. Methods: All admitted patients aged <18 years diagnosed with acute mastoiditis between 2008 and 2018 at Clalit Healthcare Services were identified and a database was generated. Results: A total of 1189 and 1115 patients met the inclusion criteria, respectively. Acute mastoiditis diagnosis was confirmed in 95.2% of the patients. The incidence was 7.78 cases per 100, 000 children‐years but was significantly higher in children under 2 years of age (average of 38.31 per 100, 000 children‐years). No specific pattern was observed in the annualized incidence rate during the study period. Acute mastoiditis was significantly more common in children of Jewish descent than non‐Jewish (10.4 vs. 3.03 per 100, 000 children‐years, P  < 0.001) and of high socioeconomic status and is more common in the winter. The prevalence of household parental smoking (52%) was more than double that previously reported in the Israeli population. Conclusions: A higher incidence of acute mastoiditis was observed in the Israeli population than in other reports. The age‐dependent rate was identified along with unique epidemiological features such as seasonality, higher incidence in patients of Jewish descent, or high socioeconomic status. Related parental smoking habits lend further support against the exposure of young children to household smoking. Level of evidence: Individual retrospective cohort study. Abstract : This large‐scale retrospective study from Israel included 1189 cases of pediatric acute mastoiditis in a 10‐year period. Looking deeper into the population, we found a high incidence of 7.78 to 100, 000 children which was shown to be much higher in children with specific epidemiologic features, such as age under 2 years and parental smoking.